E a luta continua: propostas para uma teologia pública libertadora para o desenvolvimento construída em diálogo com a reflexão teológica sul-africana - Buttelli, Felipe Gustavo Koch (2013)
This doctoral dissertation seeks to point out some ways for a public theology in a Brazilian context so that it maintains identification with the Latin American theological tradition of liberation theology. To achieve this objective, dialogue with the South African post-apartheid theological reflection was used as a resource tool, which, as we will try to show, took a similar way in the formulation of public theologies more suitable for the democratic context. Initially, we will offer an historical overview of South Africa, as well as a brief reflection about the political transition which resulted in the actual democratic context. In the second chapter some sociopolitical features of South Africa will be mentioned during and after the presidential terms of Nelson Mandela and Thabo Mbeki. Some actual challenges will be pointed out, showing similarities with the challenges faced in Brazil. In the third chapter we will offer a reading of the signs of the times by contemporary South African theologians, identifying some challenges for theology and the church in the current context. In the fourth chapter we will show, besides a brief introduction to some perceptions of public theology, a mapping of three types of South African public theologies: anti-apartheid theologies, transition theologies, and the actual public theology. In the last chapter an approach will be made which considers public theology as theology for development, identifying ways through which this public theology remains connected to the tradition of liberation theology and still presents an adequate approach to the challenges of the Brazilian and South African democratic contexts.